1995
DOI: 10.1074/jbc.270.51.30428
|View full text |Cite
|
Sign up to set email alerts
|

Interference of PR-bound RNA Polymerase with Open Complex Formation at PRM Is Relieved by a 10-Base Pair Deletion between the Two Promoters

Abstract: Bacteriophage promoters P R and P RM direct RNA synthesis in divergent orientations from start sites 82 base pairs apart. We had previously determined that the presence on the same DNA fragment of a wild type P R promoter interfered with the utilization of the P RM promoter. The results reported here concern the effects of changing the distance between the start sites by insertion or deletion of 5 or 10 base pairs. Three different techniques (run-off transcription, gel mobility shift, and permanganate probing)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Under favorable conditions, the distribution of proteins between several nucleic acid molecules can be monitored within a single solution 18,23 , as can the presence of complexes differing in protein stoichiometry and/or binding site distribution 7,24 . Proteins ranging in size from small oligopeptides to transcription complexes with M r ≥ 10 6 can give useful mobility shifts 25,26 and the assay works well with both highly-purified proteins and crude cell extracts 27 . These capabilities account in large part for the continuing popularity of the assay.…”
Section: Advantages and Limitations Of Emsamentioning
confidence: 99%
“…Under favorable conditions, the distribution of proteins between several nucleic acid molecules can be monitored within a single solution 18,23 , as can the presence of complexes differing in protein stoichiometry and/or binding site distribution 7,24 . Proteins ranging in size from small oligopeptides to transcription complexes with M r ≥ 10 6 can give useful mobility shifts 25,26 and the assay works well with both highly-purified proteins and crude cell extracts 27 . These capabilities account in large part for the continuing popularity of the assay.…”
Section: Advantages and Limitations Of Emsamentioning
confidence: 99%
“…Therefore, for the wild-type control region, in vitro RNA polymerase (RNAP)-p RM interactions occur almost exclusively in the context of another RNAP already bound to p R . It has been previously shown that this p R -bound RNAP interferes with open complex formation at p RM (16,17,21,34,37). The effect is not exerted at the initial binding of RNAP to the promoter but rather at a subsequent step (16, 34) that is likely a conformational change in the RNAP (9).…”
mentioning
confidence: 99%
“…Consistent with this notion, deletion of 1 bp between the Ϫ35 regions was found to further reduce the rate of open complex formation at p RM (40). However, it has also been shown that when the distance between the Ϫ35 regions of the promoters is shortened by the deletion of 10 bp (one turn of the DNA helix), unexpectedly the inhibition of open complex formation at p RM is greatly diminished (21). In other phages where the interpromoter distance at p R and p RM is even shorter, such as 434 (66 pdb between start sites) and P22 (52 pdb), concurrent occupancy of the promoters is not observed (8,41).…”
mentioning
confidence: 99%
See 2 more Smart Citations